Soil conservation knowledge in oil palm plantation among future plantation managers in international college of advanced technology Sarawak (ICATS) - Rusmah, bt Muhammad Ishak (Universiti Malaysia Sarawak, (UNIMAS), 2013)
This study is conducted to assess the level of knowledge in soil conservation among the plantation managers in paticular, the present DPM students and graduates of ICATS. The findings of the study could be used by ICATS to redesign the program curriculum and syllabus by means to prepare the DPM graduates for industrial training and subsequently to prepare them for work in the OP sector.